Dostarlimab for recurrent mismatch repair‐deficient endometrial cancer: A cost‐effectiveness study. (21st November 2022) - Dioun, Shayan; Chen, Ling; Melamed, Alexander; Gockley, Allison; St. Clair, Caryn M.; Hou, June Y.; Khoury‐Collado, Fady; Hur, Chin; Elkin, Elena; Accordino, Melissa; Hershman, Dawn L.; Wright, Jason D.
Abstract: Objective: Patients with recurrent endometrial cancer treated with carboplatin and paclitaxel whose disease progresses have few effective treatment options. Based on promising clinical trial data, the anti‐programmed cell death 1 (anti‐PD‐1) antibody dostarlimab was recently granted accelerated approval for endometrial cancer by the US Food and Drug Administration. We developed a decision model to examine the cost‐effectiveness of dostarlimab for patients with progressive/recurrent deficient mismatch repair (dMMR) endometrial cancer whose disease has progressed with first‐line chemotherapy. Design: Cost‐effectiveness study. Population: Hypothetical cohort of 6000 women with progressive/recurrent dMMR endometrial cancer. Methods: The initial decision point in the Markov model was treatment with dostarlimab, pembrolizumab or pegylated liposomal doxorubicin (PLD). Model probabilities, and cost and utility values were derived with assumptions drawn from published literature. Effectiveness was estimated as average quality‐adjusted life years (QALYs) gained. One‐way, two‐way and probabilistic sensitivity analyses were performed to vary the assumptions across a range of plausible values. Main outcome measures: The primary outcome was the incremental cost‐effectiveness ratio (ICER). Results: Pegylated liposomal doxorubicin (PLD) was the least costly strategy, at 55, 732, followed by dostarlimab (151, 533) and pembrolizumab (154, 597). Based on a willingness‐to‐pay threshold of 100, 000/QALY, PLD was cost‐effective compared with dostarlimab, with an ICER of 331, 913 per QALY gained for dostarlimab, whereas pembrolizumab was ruled out by extended dominance (less effective, more costly), compared with dostarlimab. In one‐way sensitivity analyses, dostarlimab was cost‐effective when its cost was reduced to 4905 (52% reduction). These results were robust in a variety of sensitivity analyses. Conclusions: Dostarlimab is associated with greater survival compared with other treatments for women with recurrent dMMR endometrial cancer. Although the agent is substantially more costly, dostarlimab became cost‐effective when its cost was reduced to 5489 per cycle.